Core information set for oesophageal cancer surgery. Issue 8 (18th May 2015) - Blazeby, J M; Macefield, R; Blencowe, N S; Jacobs, M; McNair, A G K; Sprangers, M; Brookes, S T; Avery, K N L; Blazeby, J M; Blencowe, N S; Brookes, S T; Elliot, J; et al.
Abstract: Background: Surgeons provide patients with information before surgery, although standards of information are lacking and practice varies. The development and use of a 'core information set' as baseline information before surgery may improve understanding. A core set is a minimum set of information to use in all consultations before a specific procedure. This study developed a core information set for oesophageal cancer surgery. Methods: Information was identified from the literature, observations of clinical consultations and patient interviews. This was integrated to create a questionnaire survey. Stakeholders (patients and professionals) were surveyed twice to assess views on importance of information from 'not essential' to 'absolutely essential' using Delphi methods. Items not meeting predefined criteria were discarded after each survey and the final retained items were voted on, in separate patient and professional stakeholder meetings, to agree the core set. Results: Some 67 information items were identified initially from multiple sources. Survey response rates were 76·5 per cent (185 of 242) and 54·8 per cent (126 of 230) for patients and professionals respectively (first round), and over 83 per cent in both groups thereafter. Health professionals rated short-term clinical outcomes most highly (technical complications), whereas patients prioritized information related to long-term benefits. The consensus meetings agreed the final set, which consisted of: in-hospital milestones to recovery, rates of open-and-close surgery, in-hospital mortality, major complications (reoperation), milestones in recovery after discharge, longer-term eating and drinking and overall quality of life, and chances of survival. Conclusion: This study has established a core information set for surgery for oesophageal cancer. Abstract : Merits wide adoption as a standard of care